A Diversity-Oriented Concise Synthesis of a New Class bi, Tri-Podal Quinoline Derivatives with Their In Silico Alpha-Amylase and Alpha-Glucosidase Binding Studies. (26th November 2022) - Hemanth Kumar, P.; Sarveswari, S.
Abstract: A new series of bi, tri-podal quinoline derivatives were synthesized by treating substituted phenols of (2-phenoxyquinolin-3-yl)methanols (5a–j ) with the brominating reagents such as 1, 2- bis (bromomethyl)benzene (6 ) and 1, 3, 5- tris (bromomethyl)-2, 4, 6-trimethylbenzene (8 ) in the presence of NaH as a base, afforded bi-podal (7a–j ) and tri-podal (9a–j ) quinoline derivatives respectively. All the newly synthesized compounds (7a –j and 9a –j ) were found to be obtained with good yield in lesser time. Generally, single quinoline core moiety possessing molecules are biologically active and were displayed wide range of applications in medicinal field, but here we have synthesized molecules with two, three quinoline moiety, and expect that definitely they may play a greater role in medicinal activities compared with single quinoline possessed molecules and all the newly synthesized bi, tri-podal molecules were subjected to molecular docking studies with alpha-amylase and alpha-glucosidase enzymes to envisage the binding efficacy with comparative studies of standard drug acarbose.